Nurse-patient relationship and its implications for retention in the PMTCT of HIV programme in Ghana: an appreciative inquiry - Susanna Aba Abraham; Sheila E. Clow (BMC, 2023)
Abstract Background Relationships established between nurses and midwives, and their patients have far-reaching implications; the most significant being their impact on the health-related outcomes of patients. These relationships are especially relevant in the Prevention of Mother-to-Child Transmission (PMTCT) of Human Immunodeficiency Virus (HIV) programme as women, diagnosed with HIV navigate the emotional and psychological effects of their diagnosis while carrying pregnancies. This study aimed to explore the relationships between nurses, midwives and mothers diagnosed with HIV and its impact on retention in the PMTCT Programme. Methods An Appreciative Inquiry approach that employed qualitative research methods was conducted among twenty-four participants made up of 12 HIV positive mothers, and eight midwives and four community health nurses engaged in the PMTCT programme. Individual generative interviews were conducted among the mothers while paired interviews were conducted among the health professionals. Thematic analysis guided by Colaizzi's approach was conducted. Results Three main themes emerged each with its subthemes. Under Establishing Rapport, two sub-themes emerged; making the connection and building trusting relationships. The second theme, Journeying Together, describes how the nurse-patient relationship evolved as the participant engaged in the programme; sub-themes include developing mutual goals, impactful communication, and showing commitment and building self-worth. The third theme; Ending the professional relationship details two sub-themes; continuity of care across the cascade, and termination of care which proved unsuccessful in some relationships due to blurring professional boundaries. Conclusions The nurse-patient relationship in the PMTCT programme evolved as the relationship progressed along the PMTCT cascade. Strengthening of the nurse-patient relationships was underscored by building trust through the maintenance of confidentiality, setting mutual goals, shared emotional experiences and personal stories, and building clients' self-worth. Therefore, there is a need to ensure that professional boundaries are set and maintained to reduce the occurrence of over-dependence of the clients and burnout of the nurses.